2019
DOI: 10.1016/j.chemosphere.2018.10.092
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and compositional patterns of polycyclic aromatic hydrocarbons (PAHs) and their derivatives in three edible fishes from Kharg coral Island, Persian Gulf, Iran

Abstract: This is the first report on bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) and their derivatives (oxygen, nitrogen, sulfur, hydroxyl, carbonyl and methylcontaining PAHs) in three edible marine fishes, namely Lutjanus argentimaculatus, Lethrinus microdon and Scomberomorus guttatus, from Kharg Island, Persian Gulf, Iran. The concentrations (ng g−1dw) of Σ39PAHs resulted significantly higher in fish liver than muscle, with the PAH composition pattern dominated by low molecular weight compounds (naphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 108 publications
4
28
0
Order By: Relevance
“…Since PAHs are lipophilic compounds, tissue distributions of PAHs are correlated with lipid contents. Jafarabadi et al [139] and Yu et al [162] detected positive correlations between lipid contents and total PAH concentrations in marine fish, which reflected that lipid content was the important factor for tissue-specific accumulation. However, Frapiccini et al [98], Soltani et al [163], and Zhao et al [142] detected extremely weak positive correlations or no correlations between lipid content and PAH concentrations in the tissues of fish.…”
Section: Bioaccumulation Of Pahs In Fishmentioning
confidence: 95%
See 3 more Smart Citations
“…Since PAHs are lipophilic compounds, tissue distributions of PAHs are correlated with lipid contents. Jafarabadi et al [139] and Yu et al [162] detected positive correlations between lipid contents and total PAH concentrations in marine fish, which reflected that lipid content was the important factor for tissue-specific accumulation. However, Frapiccini et al [98], Soltani et al [163], and Zhao et al [142] detected extremely weak positive correlations or no correlations between lipid content and PAH concentrations in the tissues of fish.…”
Section: Bioaccumulation Of Pahs In Fishmentioning
confidence: 95%
“…For example, fish are considered to have a higher metabolism capacity and can metabolize/depure PAHs quickly; therefore, a generally positive correlation between the concentration of PAHs in the body and the K ow value is not observed in higher trophic-level fish [134]. Additionally, several previous studies suggested that species differences in the metabolism capacity of PAHs are strongly suggested for fish and invertebrates [138][139][140]. These differences may be caused by species differences in intake pathway and efficiency, capacity of xebiotics to metabolize, and ability of depuration/excretion.…”
Section: General Trend Of the Bioaccumulation Of Pahs In Aquatic Orgamentioning
confidence: 99%
See 2 more Smart Citations
“…Polycyclic aromatic hydrocarbons (PAHs) are a family of pollutants formed by the imperfect combustion of fossil fuels and organic matter such as wood and grass; they can also naturally occur in petroleum derivates [1]. Because of their environmental hazards and health risks to humans and marine life [2][3][4][5][6], the US Environmental Protection Agency (USEPA) has listed them as priority pollutants [7,8]. Determining the environmental behavior and distribution of PAHs is important for the assessment, management and protection of wildlife health in various environments.…”
Section: Introductionmentioning
confidence: 99%